Strategi Pengembangan Pemasaran Produk Hortikultura pada PT Sumber Alam Jaya Perkasa - Nantheni, Sobha; Budiman, Irwan (Ecobuss, 2024)
This study aims to determine the application and alternative marketing strategies for horticultural products so that the company can increase sales. The method used in this research uses desciptive analysis with a quantitative approach. The data collection technique used a questionnaire method with a sample of 22 respondents. In addition, there is additional supporting data from books and other sources related to the research. The data obtained was then analyzed using the SWOT analysis method to determine the strengths, weaknesses, opportunities, and threats of the company’s marketing strategy. The results of the study as shown in the Cartesian diagram that the company is in quadrant I which supports an aggressive growth strategy (Growth Oriented Strategy) which is a very favorable situation because it has strengths and can take advantage of existing opportunities.